Josef Albers in Mexico - Albers, Josef 1888-1976; Hinkson, Lauren; Barriendos Rodríguez, Joaquín 1973- (Guggenheim, 2017)
On his first trip to Mexico, in 1935, Josef Albers (1888-1976) encountered the magnificent architecture of ancient Mesoamerica. He later remarked in a letter to Vasily Kandinsky, a former colleague at the Bauhaus, Mexico is truly the promised land of abstract art. With his wife, artist Anni Albers (1899-1994), Josef Albers visited Mexico and other Latin American countries nearly a dozen times from 1935-67. They saw numerous archeological sites and monuments, especially in Mexico and Peru. On each visit, he took hundreds of black-and-white photographs of the pyramids, shrines, and sanctuaries at these sites, often grouping multiple images printed at various scales onto 8 by 10 inch sheets. Albers's experiences in Latin America offer an essential context for understanding his paintings and prints, particularly from his Homage to the Square and Variant/Adobe series, examples of which are featured in this show. Exhibition: Solomon R. Guggenheim Museum, New York, United States (03.11.2017 - 18.02.2018).